1993
DOI: 10.1152/ajpheart.1993.264.5.h1360
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia slightly raises blood volume and sizably elevates flow velocity in brain microvessels

Abstract: The increase in local cerebral blood flow (LCBF) caused by hypercapnia may be mainly accomplished by raising the velocity of plasma and/or red blood cell (RBC) flow through the microvessels and not by perfusing more capillaries. This suggestion was tested in awake rats exposed to 8% CO2 and in control rats. LCBF was measured by the 14C-labeled iodoantipyrine method. The volume of blood in small parenchymal microvessels was estimated from the distribution spaces of 125I-labeled serum albumin (RISA) and 55Fe-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 0 publications
6
49
0
Order By: Relevance
“…In the second case, ␤ was set to 1.0, so that the microvascular bed was not distensible, and all flow changes were matched by velocity changes in the microvascular bed. As we shall briefly discuss below, the case for rat microvascular bed almost certainly lies between these two extrema (33)(34)(35). The quantity ␣ was adjusted so that, for an assumed value of ␤, the protons of water in a 0.5 mm-long exchange microvessel with flow equivalent to 100 ml/100 g-min would traverse the exchange microvessel in 0.6 sec.…”
Section: Methods: Ancillary Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second case, ␤ was set to 1.0, so that the microvascular bed was not distensible, and all flow changes were matched by velocity changes in the microvascular bed. As we shall briefly discuss below, the case for rat microvascular bed almost certainly lies between these two extrema (33)(34)(35). The quantity ␣ was adjusted so that, for an assumed value of ␤, the protons of water in a 0.5 mm-long exchange microvessel with flow equivalent to 100 ml/100 g-min would traverse the exchange microvessel in 0.6 sec.…”
Section: Methods: Ancillary Assumptionsmentioning
confidence: 99%
“…The quantity ␣ was adjusted so that, for an assumed value of ␤, the protons of water in a 0.5 mm-long exchange microvessel with flow equivalent to 100 ml/100 g-min would traverse the exchange microvessel in 0.6 sec. This typical transit time was derived from a consideration of previous work, which demonstrated that typical mean transit times for water were on the order of 600 ms for flows of 100 ml/100 g-min (34,36).…”
Section: Methods: Ancillary Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in cerebral blood volume (CBV) during hypercapnia has been shown in animals to be less than the increase in CBF (Bereczki et al, 1993;Grubb et al, 1974;Keyeux et al, 1995;Lee et al, 2001). The degree of decrease in CBV during hypocapnia has also been shown in animals to be less than that in CBF (Grubb et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…This "recruitment" could, however, be due partly to some dilation of not only arterioles and venules but also capillaries, as was recently reported by Atkin son et al (1990) and Duelli and Kuschinsky (1993). The volume of a blood vessel is proportional to its radius squared (?-), whereas the surface area is pro portional to r. Microvessel dilation would thus have less effect on S (and the PS product) (Chen et al , 1994b) than on microvessel blood volume (Shockley and LaManna, 1988;Bereczki et al, 1993b). Ac cordingly, the PS product appears to be a better indicator of capillary recruitment than does the mi crovessel blood volume, and the findings of little or no capillary recruitment by Chen et al seem to be more reliable than the reports of some capillary re cruitment by Shockley and LaManna and Bereczki et al To summarize for hypoxia, the capillary-labeling studies of Weiss and colleagues all show a near dou bling of the number of perfused capillaries in a va riety of brain regions, but these data have been se verely questioned on technical grounds by Kuschin sky and Paulson.…”
Section: Capillary Recruitment Hypothesismentioning
confidence: 99%